The Impact of a Rights-Based Counselling Intervention to Reduce Stigma in People Affected by Leprosy in Indonesia. - Mimi Lusli; Ruth Peters; Wim van Brakel; Marjolein Zweekhorst; Sorana Iancu; Joske Bunders; Irwanto; Barbara Regeer (Public Library of Science (PLoS), 2016)
BACKGROUND:This paper assesses the impact of a counselling intervention on reducing leprosy-related stigma in Cirebon District, Indonesia. The unique features of this intervention are its rights-based approach, the underlying Cognitive Behavioural Therapy (CBT) model, the three types of counselling and the lay and peer counsellors who were involved. METHODOLOGY/PRINCIPAL FINDINGS:Mixed methods (e.g. three scales, interviews, focus group discussions and reflection notes) were used to assess the impact of the intervention, which ran over a two-year period. There was a control area with no interventions. The study participants were people affected by leprosy and other key persons (e.g. family members). The sample size differs per method, for example, data regarding 67 counselling clients and 57 controls from a cohort, and notes from 207 counselling clients were examined. The notes showed that most clients faced stigma on a daily basis, whether internalized, anticipated and/or enacted. A significant reduction was found between the before and after total scores of the SARI Stigma Scale (p-value < 0.001), Participation Scale Short (p-value < 0.001) and WHO Quality of Life score (p-value < 0.001) among the counselling clients. While there is also an effect in the control group, it is much larger in the intervention group. Qualitative data indicates that knowledge and rights trigger change. Clients took steps to improve their life such as re-connecting with neighbours, helping in household activities and applying for jobs. Challenges include the wish to conceal their condition. CONCLUSION/SIGNIFICANCE:The findings show that the counselling intervention was effective in reducing stigma, promoting the rights of people with leprosy and facilitating their social participation. More research is needed on how to create a more sustainable intervention, preferably structurally embedded in the health or social services.